Physicochemical characterization and microbiology of wheat and rye flours - Cardoso, Rossana V.C. (2018)
Seven types of wheat and rye flours were studied regarding their physical and chemical properties, as well as the presence of mycotoxins and microorganisms. The results revealed that flours presented moisture and ash contents below the recommended maximum limit. They also presented a low lipid content, which helps avoiding changes in the flours’ smell and taste. From the microbiological analysis, comparing the refined rye and wheat flours, the counting in the analysed microorganisms was not significantly different. The whole flours presented high contents in almost all the tested microorganisms, highlighting the molds counting for the whole wheat flour and the aerobic plate counting for the whole rye flour. None of the samples presented Salmonella spp. Aflatoxins and ochratoxin A were not detected in any of the flours. To the best of our knowledge, this is the first characterization of wheat and rye flours for Portuguese consumers.